Desain Sistem Kontrol Umpan Balik pada Lintasan Traktor Tanpa Operator - Lilik Sutiarso; T. Takigawa (agriTECH, 2002)
In the terms of precision farming system, this research was carried out in order to develop a trajectory path control method for the autonomous tractor when approaching a target. Firstly, open loop control was considered to design a trajectory control algorithm directly, definitely and simply structure. A proposed trajectory control algorithm called parallel parking theory was developed as non-linear state equation within non-holonomic constraint. To stabilize non-linear controlled, the algorithm was derived using the state feedback linerization technique. The vehicle posture can be expressed into position, direction angle and steering angle. In a front-wheel steering vehicle, two controlling inputs, running speed and steering vehicle, two controlling inputs, running speed and steering angle. Due to the running speed is difficult to control accurately, thus only the steering angle was controlled. In order to achieve the research objective, research work was carried out to compare the performance developed control algorithm between feedback and open-loop control system. A twenty-nine Ps computer-controlled tractor with four-wheel steering and four-wheel drive was used in this research ecperiment. For local based positioning method, fan beam laser sensor,fiber optic gyro sensor and incremental type rotary encoder were installed properly on the vehicle. The experimental results showed that after modifying of the developed algorithm into a feedback control form by correcting vehicle direction angle and lateral moving distance had improved its accuracy varied up to about 95%.